2021
DOI: 10.1016/j.ymthe.2020.11.024
|View full text |Cite
|
Sign up to set email alerts
|

M2 Macrophage-Derived Exosomes Promote Angiogenesis and Growth of Pancreatic Ductal Adenocarcinoma by Targeting E2F2

Abstract: Pancreatic ductal adenocarcinoma (PDAC), one of the most aggressive tumors all over the world, has a generally poor prognosis, and its progression is positively correlated with the density of blood vessels. Recently, tumor-associated macrophages (TAMs) were proven to be beneficial for angiogenesis, but their mechanism of action remains unclear. Our study indicated that M2 macrophages were positively correlated with the microvessel density (MVD) of PDAC tissues, and M2 macrophage-derived exosomes (MDEs) could p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
110
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(127 citation statements)
references
References 39 publications
1
110
0
Order By: Relevance
“…As can be observed in Figure 6 , the coculture of EPCs with control RAW macrophages or M2d angiogenic macrophages produced a decrease or increase in VEGFR2 expression, respectively, when compared to monocultured EPCs. Although these changes were not statistically significant, they are in line with previous results by other authors who demonstrated that anti-inflammatory M2, but not proinflammatory M1 macrophages, promote angiogenesis in vivo [ 50 , 51 ].…”
Section: Resultssupporting
confidence: 90%
“…As can be observed in Figure 6 , the coculture of EPCs with control RAW macrophages or M2d angiogenic macrophages produced a decrease or increase in VEGFR2 expression, respectively, when compared to monocultured EPCs. Although these changes were not statistically significant, they are in line with previous results by other authors who demonstrated that anti-inflammatory M2, but not proinflammatory M1 macrophages, promote angiogenesis in vivo [ 50 , 51 ].…”
Section: Resultssupporting
confidence: 90%
“…Horizontal transfer of miRNAs results in enhanced tube formation ability of mouse aortic endothelial cells, mediated through downregulation of transcription factor E2F2. Interestingly, injection of TAM sEVs also promotes angiogenesis in vivo, as reflected in a significant increase in microvascular density of pancreatic tumors in a murine PDAC xenograft [113].…”
Section: Angiogenesis and Interaction With Endothelial Cellsmentioning
confidence: 99%
“…Incubation of human microvascular endothelial cells with TAM sEVs promotes angiogenesis as reflected in (1) protein levels of VEGFA, VEGFR2, ANG2, and PlGF, and (2) enhanced angiogenic ability of human microvascular endothelial cells in vitro [82]. TAM sEVs also overexpress miRNAs 155-5p and 221-5p [113]. Horizontal transfer of miRNAs results in enhanced tube formation ability of mouse aortic endothelial cells, mediated through downregulation of transcription factor E2F2.…”
Section: Angiogenesis and Interaction With Endothelial Cellsmentioning
confidence: 99%
“…Moreover, sEVs derived from M2-macrophages containing miR-155-5p and miR-221-5p further promoted angiogenesis in vitro by targeting the E2F transcription factor 2 (E2F2). Uptake of the respective sEVs in mice additionally enhanced vascular density and growth of subcutaneous tumors [ 126 ]. Transfer of M2-macrophage-sEVs with miR-365 reduced sensitivity of PDAC cells to gemcitabine in vitro and in vivo, enhancing migration and invasion of PDAC cells by targeting B-cell translocation gene 2 (BTG2) and activating FAK/AKT signaling [ 127 ].…”
Section: Sev-mediated Crosstalk Of Pdac and Associated Cells In The Tmementioning
confidence: 99%